1999
DOI: 10.1006/frne.1998.0173
|View full text |Cite
|
Sign up to set email alerts
|

Stress and the Aging Hippocampus

Abstract: The ''glucocorticoid cascade hypothesis'' of hippocampal aging has stimulated a great deal of research into the neuroendocrine aspects of aging and the role of glucocorticoids, in particular. Besides strengthening the methods for investigating the aging brain, this research has revealed that the interactions between glucocorticoids and hippocampal neurons are far more complicated than originally envisioned and involve the participation of neurotransmitter systems, particularly the excitatory amino acids, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
98
1
11

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(116 citation statements)
references
References 141 publications
(193 reference statements)
3
98
1
11
Order By: Relevance
“…In addition, actin filament was more stable in Asp 78,82 -hsp27 (mimics the phosphorylated form) transfected HiB5 cells than in the normal and Ala 78,82 -hsp27 (nonphosphorylative form) transfected cells. In accordance with actin filament stability, the survival rate against the heat shock increased markedly in Asp 15,78,82 -hsp27 expressing HiB5 cells but decreased in Ala 15,78,82 -hsp27 expressing cells. These results support the idea that phosphorylation of HSP25 is critical for the maintenance of actin filament and enhancement of thermoresistance.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…In addition, actin filament was more stable in Asp 78,82 -hsp27 (mimics the phosphorylated form) transfected HiB5 cells than in the normal and Ala 78,82 -hsp27 (nonphosphorylative form) transfected cells. In accordance with actin filament stability, the survival rate against the heat shock increased markedly in Asp 15,78,82 -hsp27 expressing HiB5 cells but decreased in Ala 15,78,82 -hsp27 expressing cells. These results support the idea that phosphorylation of HSP25 is critical for the maintenance of actin filament and enhancement of thermoresistance.…”
mentioning
confidence: 65%
“…Hippocampus is a brain region most vulnerable to a variety of environmental stresses; various forms of stress lead to hippocampal cell damage and eventually cell death (14,15). However, little is known about protective roles of HSPs in the hippocampus.…”
mentioning
confidence: 99%
“…On the other hand, elevated corticosterone concentrations associated with a learning situation in rats improved consolidation of learned information (5, 20), whereas rises in corticosterone level out of context impair cognitive function (for review see ref. 23). In agreement with the former, we presently found that mice receiving exogenous corticosterone in context with water maze performance respond with an improvement of spatial learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Stress exposure may induce deleterious effects on brain structure and cognition [1,2] and increase the risks of developing neuropsychiatric disorders [3]. Noise exposure exceeds 90 dB has been reported to be a source of stressor [4].…”
Section: Introductionmentioning
confidence: 99%